Diffusion of Sodium Diclofenac from Carbopol 940 Gel at Various pH - Ketut Widyani Astuti; Yeyet C. Sumirtapura; Ni Nyoman Wiwik S (Pharmacy Department, Math and Sciences Faculty, Udayana Univerity, 2012)
Diffusion of sodium diclofenac in Carbopol 940 gel has been investigated. Diffusion test was performed in diffusion cells with artificial membranes of Whatman no.1 filter paper which immersed with Spangler solution. Measurement of active ingredient concentration that diffuses was performed using UV spectrophotometer at a wavelength of 277 nm. The results showed that diffusion rate of sodium diclofenac from Carbopol gel increased at higher pH. The highest diffusion of diclofenac sodium occurs at pH 8 with a mean percentage of diclofenac sodium which diffuses after 240 minutes was 48.06 + 4.83%. The mean percentage of diclofenac sodium which diffuses from the gel Carbopol 940 at pH 6 after 240 minutes was 11.47 + 1.71% while the Carbopol 940 gel at pH 7 is 22.44 + 3.71%. Key words: Diffusion; Diclofenac sodium; pH; gel Carbopol 940